The Spatial Transformation of Traditional Rural Villages Driven by Private Investment in Chinaâs Developed Areas: The Case of Daxi Village, Anji County - Simin Yan; Chen Chen (Journal of Regional and City Planning, 2018)
Abstract. Restricted by political ideology and institutional barriers, the development of rural China has in the past relied heavily on government spending. However, with institutional reform and the development of a market economy, private investment is playing an increasingly important role in rural development, especially in traditional rural villages. Daxi village in Anji County of Zhejiang Province is a typical case. Investment in the Tianhuangping Hydropower Station and the Beautiful Villlages policy supported by the public sector (government and state-owned enterprises) have been important driving forces in attracting private investments in rural tourism and have had a profound impact on the physical, economic and social space of Daxi village. This research used interviews with key subjects, including government officials, non-local investors and returned migrants, and a questionnaire survey among local residents. It was found that with the growth of private investment, location, transportation, natural resources, development policies and superior human resources are the most important factors that drive spatial transformation. Finally, it also offers a discussion on how the Daxi model may shed light on rural development in developing countries with an urban-rural dichotomy.Keywords. spatial transformation, private investment, rural development, Daxi village.Abstrak. Dibatasi oleh ideologi politik dan hambatan institusional, perkembangan pedesaan Cina di masa lalu sangat bergantung pada belanja pemerintah. Namun, dengan reformasi kelembagaan dan pengembangan ekonomi pasar, investasi swasta memainkan peran yang semakin penting dalam pembangunan pedesaan, terutama di desa-desa pedesaan tradisional. Desa Daxi di Kabupaten Anji, Provinsi Zhejiang adalah kasus yang tipikal. Investasi di Stasiun Pembangkit Listrik Tenaga Air Tianhuangping dan kebijakan Desa Indah yang didukung oleh sektor publik (pemerintah dan badan usaha milik negara) telah menjadi dorongan yang penting dalam menarik investasi swasta pada pariwisata pedesaan dan memiliki dampak besar pada ruang fisik, ekonomi dan sosial Desa Daxi. Penelitian ini menggunakan wawancara dengan subyek-subyek utama, termasuk pejabat pemerintah, investor non-lokal dan migran yang telah kembali, dan survei kuesioner di antara penduduk setempat. Ditemukan bahwa dengan pertumbuhan investasi swasta, lokasi, transportasi, sumber daya alam, kebijakan pembangunan dan sumber daya manusia yang unggul adalah faktor paling penting yang mendorong transformasi spasial. Akhirnya, penelitian ini juga menawarkan diskusi tentang bagaimana model Daxi dapat menjelaskan perkembangan pedesaan di negara-negara berkembang dengan dikotomi kota-desa.Kata kunci. transformasi spasial, investasi swasta, pembangunan pedesaan, Desa Daxi.